2018
DOI: 10.1177/1744806917754142
|View full text |Cite
|
Sign up to set email alerts
|

Lithium reverses mechanical allodynia through a mu opioid-dependent mechanism

Abstract: BackgroundLithium is widely used to treat bipolar disorders and displays mood stabilizing properties. In addition, lithium relieves painful cluster headaches and has a strong analgesic effect in neuropathic pain rat models.ObjectivesTo investigate the analgesic effect of lithium on the cuff model of neuropathic pain.MethodsWe used behavioral and pharmacological approaches to study the analgesic effect of a single injection of lithium in wild-type and mu opioid receptor (MOR) null cuffed neuropathic mice. Mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…The current study showed that single treatment of NP in experimental animals with either LiCl or Vit E mitigated the development of mechanical hyperalgesia in CCI‐induced Wistar rats. These were consistent with previous studies on laboratory animal model of NP 12,17,21 . Combined treatment with Vit E and LiCl showed a more robust anti‐nociceptive effect on CCI‐induced NP in Wistar rats.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The current study showed that single treatment of NP in experimental animals with either LiCl or Vit E mitigated the development of mechanical hyperalgesia in CCI‐induced Wistar rats. These were consistent with previous studies on laboratory animal model of NP 12,17,21 . Combined treatment with Vit E and LiCl showed a more robust anti‐nociceptive effect on CCI‐induced NP in Wistar rats.…”
Section: Discussionsupporting
confidence: 92%
“…These were consistent with previous studies on laboratory animal model of NP. 12,17,21 Combined treatment with Vit E and LiCl showed a more robust anti-nociceptive effect on CCIinduced NP in Wistar rats. This indicates a strong synergistic interaction between Vit E and LiCl.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Lithium often reduces the attack frequency in CH, refs. [56][57][58] and it attenuated allodynia for heat, cold, and mechanical stimuli in animal experiments [59][60][61]. Finally, animal studies on CGRP receptor antagonists suggest an impact on hyperalgesia, as well [62].…”
Section: The Influence Of Prophylactic Treatmentmentioning
confidence: 87%